Nonaqueous electrolyte and lithium secondary battery including same

By using non-aqueous electrolytes containing lithium salts, organic solvents and lithium difluoro(oxalic acid) borate in lithium secondary batteries, the problem of side reactions on the positive electrode surface at high voltage and high temperature is solved, and the circulation and storage performance of the battery is significantly improved. , reduces gas production and extends battery life.

CN119213601APending Publication Date: 2024-12-27LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380040433.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-08-31
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Under high voltage and high temperature conditions, the film or electrode surface structure formed on the positive electrode surface of the lithium secondary battery is formed due to side reactions caused by electrolyte deterioration, causing the dissolution of transition metal ions, which damages the SEI film of the negative electrode, thereby affecting the cycling performance and stability of the battery. , and the battery may generate gas at high temperatures to cause expansion.

Method used

A non-aqueous electrolyte is used, which comprises lithium salts, organic solvents and additives, wherein the additives include lithium difluoro (oxalic acid) borate (LiODFB) and specific diisocyanate compounds, combined with ethylene carbonate, propylene carbonate, Ethylene propionate and propionate propionate help inhibit the decomposition of lithium salt and the production of by-products, stabilize the positive electrode film, reduce gas production, and prevent negative electrode deterioration.

Benefits of technology

It effectively suppresses the deterioration of the positive electrode and the passivation of the SEI film of the negative electrode, improves the high-temperature circulation and storage performance of the lithium secondary battery, extends the battery life, and reduces the gas production at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119213601A_ABST
    Figure CN119213601A_ABST
Patent Text Reader

Abstract

The present invention provides a non-aqueous electrolyte including a lithium salt, an organic solvent, and an additive, in which the additive includes a compound represented by the following Formula 1 and lithium difluoro (oxalate) borate (LiODFB), and the organic solvent includes ethylene carbonate (EC), propylene carbonate (PC), ethylene propionate (EP), and propyl propionate (PP). In Formula 1, n is an integer from 3 to 10. [Formula 1] # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0110317 filed on August 31, 2022, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0003] The present invention relates to a non-aqueous electrolyte and a lithium secondary battery comprising the same. Background Art

[0004] Recently, in order to obtain higher capacity of lithium secondary batteries, attempts have been made to drive the secondary batteries at higher voltages.

[0005] However, when the secondary battery is driven at a high voltage, as charging and discharging proceed, the film or electrode surface structure formed on the surface of the positive electrode / negative electrode deteriorates due to side reactions caused by electrolyte degradation, so that transition metal ions can be dissolved from the surface of the positive electrode. The transition metal ions dissolved as described above are electrodeposited on the negative electrode and reduce the passivation ability of SEI, thereby causing the problem of negative electrode degradation.

[0006] This degradation phenomenon of the secondary battery tends to accelerate as the potential of the positive electrode increases or when the battery is exposed to high temperature, thereby causing a problem in that the cycle performance of the secondary battery deteriorates due to the degradation phenomenon.

[0007] In addition, when a lithium secondary battery is continuously used for a long time or left at high temperature, gas is generated and causes a so-called swelling phenomenon, that is, an increase in battery thickness, and it is known that the amount of gas generated at this time depends on the state of SEI.

[0008] Therefore, in order to solve the above problems, research and development have been conducted to obtain methods capable of suppressing the dissolution of transition metal ions from the positive electrode, reducing damage to the negative electrode SEI film, reducing the swelling phenomenon of the secondary battery, and improving stability at high temperatures. Summary of the invention

[0009] [Technical issues]

[0010] As a result of various studies conducted to solve the above-mentioned problems, the present invention provides a nonaqueous electrolyte capable of suppressing the degradation of a positive electrode and reducing a side reaction between the positive electrode and the electrolyte.

[0011] In addition, the present invention provides a lithium secondary battery including the nonaqueous electrolyte, thereby having improved overall performance as well as improved high-temperature cycle performance and high-temperature storage performance.

[0012] [Technical solution]

[0013] In order to achieve the above-mentioned object, the present invention provides a non-aqueous electrolyte comprising a lithium salt, an organic solvent and an additive, wherein the additive comprises a compound represented by the following formula 1 and lithium difluoro(oxalato)borate (LiODFB), and the organic solvent comprises ethylene carbonate (EC), propylene carbonate (PC), ethylene propionate (EP) and propyl propionate (PP).

[0014] [Formula 1]

[0015]

[0016] In the above Formula 1, n is an integer of 3 to 10.

[0017] [Beneficial Effects]

[0018] The non-aqueous electrolyte of the present invention includes the compound represented by the above formula 1 and lithium difluoro(oxalate)borate (LiODFB), thereby suppressing the decomposition of the lithium salt and suppressing the positive electrode collapse caused by byproducts such as HF. In addition, the degradation of the passivation ability of SEI at high temperature can be suppressed, thereby preventing the degradation of the negative electrode.

[0019] Specifically, the combination of the diisocyanate compound of Formula 1 and lithium difluoro (oxalic acid) borate (LiODFB) can stabilize the electrolyte, so the decomposition reaction of carbonate solvents and propionate solvents can be suppressed. In addition, in an environment where a stable positive electrode film formed by a combination of a diisocyanate compound of Formula 1 and lithium difluoro (oxalic acid) borate (LiODFB) is fully formed, ethylene propionate (EP) and propyl propionate (PP) have low reactivity with oxygen deintercalated from the positive electrode material, so carbon dioxide (oxidizing gas) is suppressed. As a result, in a lithium secondary battery including a nonaqueous electrolyte of the present invention, gas generation at high temperature can be suppressed. That is, when using the nonaqueous electrolyte of the present invention, the dissolution of transition metals from the positive electrode is suppressed to maintain a higher high temperature durability, thereby improving high temperature cycle performance and high temperature storage performance, and realizing a lithium secondary battery with improved overall performance. DETAILED DESCRIPTION

[0020] It should be understood that the words or terms used in the specification and claims of the present invention should not be interpreted as limited to the meanings defined in commonly used dictionaries. It should also be understood that based on the principle that the inventor can appropriately define the meaning of words or terms to best explain the present invention, words or terms should be interpreted as having a meaning consistent with their meanings in the context of the relevant technology and the technical idea of ​​the present invention.

[0021] In this specification, it should be understood that the terms "include", "comprises" or "has" are intended to specify the presence of stated features, numbers, steps, elements or a combination thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements or a combination thereof.

[0022] In addition, in this specification, it should be understood that when describing "carbon atoms a to b" in this document, "a" and "b" refer to the number of carbon atoms contained in a particular functional group. That is, the functional group may include "a" to "b" carbon atoms. For example, "alkylene having 1 to 5 carbon atoms" refers to an alkylene containing carbon atoms having a carbon number of 1 to 5, i.e., -CH2-, -CH2CH2-, -CH2CH2CH2-, -CH2(CH3)CH-, -CH(CH3)CH2-, and -CH(CH3)CH2CH2-, etc.

[0023] In addition, in the present specification, alkyl groups may be all substituted or unsubstituted. Unless otherwise defined, the term "substituted" refers to at least one hydrogen bonded to carbon being substituted by an element other than hydrogen, for example, it refers to an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an alkynyl group having 2 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, a cycloalkenyl group having 3 to 12 carbon atoms, a heterocycloalkyl group having 3 to 12 carbon atoms, a heterocycloalkenyl group having 3 to 12 carbon atoms, an aryloxy group having 6 to 12 carbon atoms, a halogen atom, a fluoroalkyl group having 1 to 20 carbon atoms, a nitro group, an aryl group having 6 to 20 carbon atoms, a heteroaryl group having 2 to 20 carbon atoms, or a halogenated aryl group having 6 to 20 carbon atoms, etc.

[0024] Hereinafter, the present invention will be described in more detail.

[0025] Non-aqueous electrolytes

[0026] The nonaqueous electrolyte of the present invention includes a lithium salt, an organic solvent and an additive, wherein the additive may include a compound represented by the following Formula 1 and lithium difluoro(oxalato)borate (LiODFB), and the organic solvent may include ethylene carbonate (EC), propylene carbonate (PC), ethylene propionate (EP) and propyl propionate (PP).

[0027] [Formula 1]

[0028]

[0029] In the above Formula 1, n may be an integer from 3 to 10. Preferably, n in the above Formula 1 may be an integer from 3 to 8.

[0030] The compound of formula 1 is a compound substituted with an isocyanate group at the end, which can form a complex with a lithium salt to stabilize the lithium salt, thereby suppressing the generation of by-products such as HF. As a result, the dissolution of transition metals, especially cobalt, from the positive electrode can be suppressed. When the dissolution of transition metals from the positive electrode is suppressed, the degradation of the positive electrode is suppressed, thereby improving the cycle performance and storage performance. Since the degradation of the positive electrode becomes more serious at a higher temperature, when the non-aqueous electrolyte of the present invention is used, the cycle performance and storage performance at high temperature can be improved.

[0031] Since lithium difluoro(oxalato)borate (LiODFB) can stabilize the anode interface through a fast anode reduction reaction, it can improve the cycling performance and storage performance at high temperature.

[0032] In the non-aqueous electrolyte of the present invention, based on 100 parts by weight of the non-aqueous electrolyte, the content of the compound represented by the above formula 1 can be 0.1 parts by weight to 5 parts by weight, preferably 0.1 parts by weight to 3 parts by weight, and more preferably 0.1 parts by weight to 2 parts by weight. When the content of the compound of formula 1 satisfies the above range, the effect of inhibiting the dissolution of transition metals from the positive electrode is sufficient, thereby having the effect of excellent life performance at high temperature and high temperature storage performance.

[0033] In the non-aqueous electrolyte of the present invention, based on 100 parts by weight of the non-aqueous electrolyte, the content of lithium difluoro(oxalate)borate (LiODFB) can be 0.1 parts by weight to 5 parts by weight, preferably 0.1 parts by weight to 3 parts by weight, and more preferably 0.1 parts by weight to 2 parts by weight. When the content of LiODFB satisfies the above range, the change of the negative electrode modification is sufficient due to the rapid negative electrode reduction decomposition reaction in the activation step, so that the life performance and high temperature storage performance are excellent.

[0034] In the non-aqueous electrolyte of the present invention, the compound represented by Formula 1 and lithium difluoro(oxalato)borate (LiODFB) may be included in a weight ratio of 0.2: 1 to 5: 1, preferably 1: 1 to 5: 1, and most preferably 1: 1 to 3: 1. When the additive of Formula 1 and LiODFB are included in the above range, the pH of the electrolyte is in an appropriate range, and the decomposition of the lithium salt is appropriately suppressed, so that the dissolution of transition metals, particularly Co, can be suppressed during high voltage charging or at high temperatures.

[0035] The non-aqueous electrolyte of the present invention may include a lithium salt. The lithium salt is used as an electrolyte salt in a lithium secondary battery and as a medium for transmitting ions. Generally, the lithium salt may include Li + as cations, and may include a group consisting of F - , Cl - Br - ,I - 、NO3 - 、N(CN)2- 、BF4 - 、ClO4 - , B 10 Cl 10 - 、AlCl4 - 、AlO2 - PF6 - CF3SO3 - 、CH3CO2 - CF3CO2 - 、AsF6 - 、SbF6 - 、CH3SO3 - 、(CF3CF2SO2)2N - 、(CF3SO2)2N - 、(FSO2)2N - 、BF2C2O4 - , BC4O8 - PF4C2O4 - PF2C4O8 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - 、C4F9SO3 - CF3CF2SO3 - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - CF3(CF2)7SO3 - , and SCN - At least one of the group consisting of is used as an anion.

[0036] Specifically, the non-aqueous electrolyte of the present invention may include LiPF6 as a lithium salt. In addition, the lithium salt may include a salt selected from the group consisting of LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10, LiAlCl4, LiAlO2, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiN(SO2F)2(lithium bis(fluorosulfonyl)imide (LiFSI)), LiN(SO2CF2CF3)2(lithium bis(perfluoroethanesulfonyl)imide (LiBETI)) and LiN(SO2CF3)2(lithium bis(trifluoromethane)sulfonyl)imide (LiTFSI)), or a mixture of two or more thereof. In addition, any lithium salt commonly used in the electrolyte of lithium secondary batteries can be used without limitation.

[0037] Although the lithium salt can be appropriately changed within a generally available range, in order to obtain the best effect of forming an anticorrosion film on the electrode surface, the lithium salt can be contained in the electrolyte at a concentration of 0.5 M to 5.0 M, preferably 1.0 M to 3.0 M, and more preferably 1.2 M to 2.0 M. When the concentration of the lithium salt satisfies the above range, the effect of improving the cycle performance of the lithium secondary battery during high temperature storage is sufficient, and the viscosity of the nonaqueous electrolyte is appropriate, so that the wettability of the electrolyte can be improved.

[0038] The non-aqueous electrolyte of the present invention may include an organic solvent containing ethylene carbonate (EC), propylene carbonate (PC), ethylene propionate (EP) and propyl propionate (PP). More preferably, the non-aqueous electrolyte of the present invention may include an organic solvent consisting of ethylene carbonate (EC), propylene carbonate (PC), ethylene propionate (EP) and propyl propionate (PP).

[0039] Ethylene carbonate (EC) and propylene carbonate (PC) are high viscosity organic solvents with high dielectric constants, so lithium salts can be well dissociated in the electrolyte. In an environment where a stable positive electrode film formed by a combination of a diisocyanate compound of Formula 1 and lithium difluoro(oxalate)borate (LiODFB) is fully formed, propyl propionate (PP) has low reactivity with oxygen deintercalated from the positive electrode material, thereby suppressing carbon dioxide (oxidizing gas). Ethylene propionate (EP) works with propyl propionate (PP) to increase lithium ion mobility, thereby having the effect of improving fast charging performance.

[0040] The non-aqueous electrolyte of the present invention includes ethylene carbonate (EC), propylene carbonate (PC), ethylene propionate (EP) and propyl propionate (PP), so that a non-aqueous electrolyte with sufficient ionic conductivity can be provided. As a result, there is an effect of excellent long-term life performance. Most preferably, the organic solvent contained in the non-aqueous electrolyte of the present invention can be composed of ethylene carbonate (EC), propylene carbonate (PC), ethylene propionate (EP) and propyl propionate (PP).

[0041] The nonaqueous electrolyte of the present invention may include at least one organic solvent selected from the group consisting of fluoroethylene carbonate (FEC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, and vinylene carbonate as other organic solvents.

[0042] Meanwhile, if necessary, the organic solvent may additionally use any organic solvent generally used in non-aqueous electrolytes without limitation. For example, at least one organic solvent of an ether organic solvent, a glyme organic solvent, and a nitrile organic solvent may be additionally included.

[0043] As the ether solvent, any one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, 1,3-dioxolane (DOL) and 2,2-bis(trifluoromethyl)-1,3-dioxolane (TFDOL) or a mixture of two or more thereof may be used, but the present invention is not limited thereto.

[0044] The glycol diether solvent is a solvent having a higher dielectric constant and lower surface tension than the linear carbonate organic solvent and lower reactivity with metals, and may include at least one selected from the group consisting of dimethoxyethane (glycol dimethyl ether, DME), diethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether (TEGDME), but is not limited thereto.

[0045] The nitrile solvent may be one or more selected from the group consisting of acetonitrile, propionitrile, butyronitrile, valeronitrile, octanonitrile, heptanecarbonitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, benzyl cyanide, 2-fluorobenzoyl cyanide, and 4-fluorobenzoyl cyanide, but is not limited thereto.

[0046] In addition, if necessary, the non-aqueous electrolyte of the present invention may also include electrolyte additives known in the art in the non-aqueous electrolyte to prevent the non-aqueous electrolyte from decomposing in a high output environment and causing negative electrode collapse, or to further improve low-temperature high-rate discharge performance, high-temperature stability, overcharge protection, and the effect of inhibiting battery expansion at high temperatures.

[0047] Representative examples of the electrolyte additive may include at least one SEI film-forming additive selected from the group consisting of cyclic carbonate compounds, halogenated carbonate compounds, sultone compounds, sulfate compounds, phosphate compounds, borate compounds, nitrile compounds, benzene compounds, amine compounds, silane compounds and lithium salt compounds.

[0048] The cyclic carbonate compound may be vinylene carbonate (VC) or vinyl ethylene carbonate.

[0049] The halogenated carbonate compound may be fluoroethylene carbonate (FEC).

[0050] The sultone compound may be at least one compound selected from the group consisting of 1,3-propane sultone (PS), 1,4-butane sultone, ethylene sultone, 1,3-propene sultone (PRS), 1,4-butene sultone, and 1-methyl-1,3-propene sultone.

[0051] The sulfate compound may be ethylene sulfate (ESA), trimethylene sulfate (TMS) or methyltrimethylene sulfate (MTMS).

[0052] The phosphate compound may be one or more compounds selected from the group consisting of lithium difluoro(bisoxalato)phosphate, lithium difluorophosphate, tetramethyltrimethylsilylphosphate, tris(trimethylsilyl)phosphite, tris(2,2,2-trifluoroethyl)phosphate and tris(trifluoroethyl)phosphite.

[0053] The borate compound may be tetraphenylborate, lithium oxalyldifluoroborate (LiODFB) and lithium bis(oxalatoborate) (LiB(C2O4)2, LiBOB).

[0054] The nitrile compound may be at least one compound selected from the group consisting of succinonitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, octanonitrile, heptanecarbonitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, benzyl cyanide, 2-fluorophenyl cyanide and 4-fluorophenyl cyanide.

[0055] The benzene compound may be fluorobenzene, the amine compound may be triethanolamine or ethylenediamine, and the silane compound may be tetravinylsilane.

[0056] The lithium salt-based compound is a compound other than the lithium salt contained in the non-aqueous electrolyte, and may be lithium difluorophosphate (LiDFP), LiPO 2 F 2 , LiBF 4 , or the like.

[0057] Among these electrolyte additives, when a combination of vinylene carbonate (VC), 1,3-propane sultone (PS), ethylene sulfate (Esa) and lithium difluorophosphate (LiDFP) is included, a stronger SEI film can be formed on the negative electrode surface during the initial activation process of the secondary battery, and gas generation that may be caused by decomposition of the electrolyte at high temperature is suppressed, thereby improving the high temperature stability of the secondary battery.

[0058] Meanwhile, two or more electrolyte additives may be mixed for use, and their content may be 0.050 to 20 wt %, specifically 0.10 to 15 wt %, preferably 0.30 to 10 wt %, based on the total weight of the non-aqueous electrolyte. When the content of the electrolyte additive satisfies the above range, the effect of improving ion conductivity and cycle performance is more excellent.

[0059] Lithium secondary battery

[0060] The present invention also provides a lithium secondary battery comprising the non-aqueous electrolyte.

[0061] Specifically, the lithium secondary battery includes: a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, a separator interposed between the positive electrode and the negative electrode, and the above-mentioned nonaqueous electrolyte.

[0062] At this time, the lithium secondary battery of the present invention can be manufactured by a common method known in the art. For example, the lithium secondary battery of the present invention can be manufactured by the following process: forming an electrode assembly stacked with a positive electrode, a negative electrode, and a separator between the positive electrode and the negative electrode in sequence, and then inserting the electrode assembly into a battery case, and then injecting the nonaqueous electrolyte of the present invention therein.

[0063] The upper limit of the operating voltage of the lithium secondary battery of the present invention is above 4.47 V and can be driven at a high voltage. The upper limit voltage of the operating voltage refers to the charge termination voltage during charge / discharge of the lithium secondary battery, such as the cut-off voltage under CC-CV charging conditions.

[0064] The lithium secondary battery of the present invention is characterized in that the amount of Co eluted is small even when driven at a high voltage. Specifically, the lithium secondary battery of the present invention can satisfy the following relational expression (1).

[0065] Relation (1): D t / D0<5

[0066] In the above equation 1, D t is the amount of Co dissolved in the non-aqueous electrolyte measured after the lithium secondary battery was stored at a high temperature of 85° C. for 8 hours, and D0 is the amount of Co dissolved in the non-aqueous electrolyte of the lithium secondary battery before high-temperature storage.

[0067] Preferably, the D of the lithium secondary battery of the present invention is t The / D0 value may be between 1.5 and 3.5, most preferably between 1.5 and 2.5.

[0068] In addition, the lithium secondary battery of the present invention is characterized in that it does not have an overly acidic pH even when driven at a high voltage. Specifically, the pH of the nonaqueous electrolyte of the lithium secondary battery of the present invention measured after storage at 60°C for 1 week may be greater than 4, preferably a pH of 4.2 to 5.

[0069] (1) Positive electrode

[0070] The positive electrode can be manufactured by coating a positive electrode mixture paste including a positive electrode active material, a binder, a conductive material, a solvent, etc. on a positive electrode current collector.

[0071] There is no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used.

[0072] The positive electrode active material is a compound capable of reversibly inserting and extracting lithium. Specifically, it may include a lithium metal oxide containing one or more metals (such as cobalt, manganese, nickel, and aluminum) and lithium. More specifically, the lithium metal oxide may be: lithium manganese-based oxides (such as LiMnO2, LiMn2O4, etc.), lithium cobalt-based oxides (such as LiCoO2, etc.), lithium nickel-based oxides (such as LiNiO2, etc.), lithium nickel manganese-based oxides (such as LiNi 1-Y Mn Y O2 (where 0 < Y < 1), LiMn 2-Z Ni Z O4 (where 0 < Z < 2), etc.), lithium nickel cobalt-based oxides (such as LiNi 1-Y1 Co Y1 O2 (where 0 < Y1 < 1), etc.), lithium manganese cobalt-based oxides (such as LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2-Z1 Co Z1 O4 (where 0 < Z1 < 2), etc.), lithium nickel manganese cobalt-based oxides (such as Li(Ni p Co q Mn r )O2 (where 0 < p < 1, 0 < q < 1, 0 < r < 1 and p + q + r = 1) or Li(Ni p1 Co q1 Mn r1 )O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r1 < 2 and p1 + q1 + r1 = 2), etc.), or lithium nickel cobalt transition metal (M) oxides (such as Li(Ni p2 Co q2 Mn r2 M s2)O2, where M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r2, and s2 are each the atomic fraction of independent elements, where 0 < p2 < 1, 0 < q2 < 1, 0 < r2 < 1, 0 < s2 < 1, and p2 + q2 + r2 + s2 = 1), etc., and may include any one or a mixture of two or more thereof.

[0073] Among them, since the capacity performance and stability of the battery can be improved, the lithium metal oxide can be LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (for example, Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.), or lithium nickel cobalt aluminum oxide (for example, Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.), and any one or a mixture of two or more thereof can be used.

[0074] Among them, the positive electrode active material can be a lithium cobalt-based oxide represented by Formula 2 below.

[0075] [Formula 2]

[0076] Li a1 Co 1-x1 M 1 x1 O 2+β

[0077] In Formula 2 above, M 1 includes one or more selected from the group consisting of Al, B, Ba, Ca, Zr, Ti, Mg, Ta, Nb, Sr, W, and Mo, 0.9 < a1 ≤ 1.1, 0 ≤ x1 ≤ 0.2, and 0 ≤ β ≤ 0.02.

[0078] Based on the total weight of the solids other than the solvent in the positive electrode mixture slurry, the content of the positive electrode active material can be 60% by weight to 99% by weight, preferably 70% by weight to 99% by weight, more preferably 80% by weight to 98% by weight.

[0079] The binder is a component used to assist bonding between active materials, conductive materials, etc., and bonding with a current collector.

[0080] Examples of the binder may include polyvinylidene fluoride, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene (PE), polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, and various copolymers thereof.

[0081] Generally, the content of the binder may be 1 to 20 wt %, preferably 1 to 15 wt %, and more preferably 1 to 10 wt %, based on the total weight of solids excluding the solvent in the positive electrode mixture slurry.

[0082] The conductive material is a component for further improving the conductivity of the positive electrode active material, and can be added in an amount of 1 to 20% by weight based on the total weight of the solid in the positive electrode mixture slurry. The conductive material is not particularly limited as long as it has conductivity without causing chemical changes in the battery, and for example, carbon powder such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black can be used; graphite powder such as natural graphite, artificial graphite, or graphite with a very developed crystal structure; conductive fibers such as carbon fibers or metal fibers; conductive powders such as fluorocarbon powders, aluminum powders, and nickel powders; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives; and the like.

[0083] Generally, the content of the binder may be 1 to 20 wt %, preferably 1 to 15 wt %, and more preferably 1 to 10 wt %, based on the total weight of solids excluding the solvent in the positive electrode mixture slurry.

[0084] The solvent may include an organic solvent, such as N-methyl-2-pyrrolidone (NMP), and its use amount may be such that a preferred viscosity is achieved when a positive electrode active material and an optional binder and a conductive material are included. For example, the content of the solvent may be such that the concentration of the solid including the positive electrode active material and the optional binder and conductive material is 50 wt % to 95 wt %, preferably 70 wt % to 95 wt %, and more preferably 70 wt % to 90 wt %.

[0085] (2) Negative electrode

[0086] The negative electrode may be manufactured by, for example, coating a negative electrode mixture slurry containing a negative electrode active material, a binder, a conductive material, a solvent, etc. on a negative electrode collector, or a graphite electrode made of carbon (C) or metal itself may be used as the negative electrode.

[0087] For example, when manufacturing a negative electrode by coating a negative electrode mixture slurry on a negative electrode current collector, the thickness of the negative electrode current collector is generally 3 to 500 μm. The negative electrode current collector is not particularly limited as long as it has high electrical conductivity without causing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloy, etc. can be used. Moreover, similar to the case of the positive electrode current collector, micro-irregularities can be formed on the surface of the negative electrode current collector to improve the binding force of the negative electrode active material, and the negative electrode current collector can be used in various forms, such as films, sheets, foils, meshes, porous bodies, foams, and non-woven fabric bodies.

[0088] In addition, the negative electrode active material may include at least one selected from the group consisting of lithium metal, a carbon material capable of reversibly inserting / extracting lithium ions, a metal or an alloy of a metal and lithium, a metal composite oxide, a material capable of doping and dedoping lithium, and a transition metal oxide.

[0089] As the carbon material capable of reversibly inserting / extracting lithium ions, the carbon-based negative electrode active material commonly used in lithium ion secondary batteries can be used without particular limitation, and its representative examples may include crystalline carbon, amorphous carbon, or a combination thereof. Examples of crystalline carbon may include graphite, such as natural graphite or artificial graphite in irregular, plate-like, flake-like, spherical, or fibrous forms, and examples of amorphous carbon may include soft carbon (low-temperature fired carbon) or hard carbon, mesophase pitch carbide, and fired coke, etc.

[0090] As the metal or the alloy of a metal and lithium, a metal selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn, or the alloy of the metal and lithium can be used.

[0091] As the metal composite oxide, one selected from the group consisting of PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, Li x Fe2O3(0≤x≤1), Li x WO2(0≤x≤1), and Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements in Group 1, Group 2, Group 3 of the periodic table, halogens; 0<x≤1; 1≤y≤3; 1≤z≤8) can be used.

[0092] Materials capable of doping and de-doping lithium can be: Si, SiO x (0 < x ≤ 2), Si-Y alloys (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, but not Si), Sn, SnO2, and Sn-Y (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, but not Sn), etc., or at least one of them can be mixed with SiO2 and used. The element Y can be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.

[0093] Transition metal oxides can be lithium-containing titanium composite oxides (LTO), vanadium oxides, and lithium vanadium oxides, etc.

[0094] When using Si or SiO x (0 < x < 2) as the negative electrode active material, the additive of the present invention is particularly effective. Specifically, when using a silicon-based negative electrode active material, if a strong SEI layer is not formed on the surface of the negative electrode during the initial activation, the large volume expansion and contraction during cycling will accelerate the deterioration of the life performance. However, the additive of the present invention can form an elastic and strong SEI layer, so the life performance and storage performance of the secondary battery using the silicon-based negative electrode active material can be improved.

[0095] Among them, the negative electrode active material can be a mixture of graphite and SiO x (0 ≤ x < 2). In terms of increasing the capacity of the lithium secondary battery, graphite and SiO x (0 ≤ x < 2) can be included in a weight ratio of 97:3 to 90:10.

[0096] Based on the total weight of the solids in the negative electrode mixture slurry, the content of the negative electrode active material can be 60 to 99 wt%, preferably 70 to 99 wt%, more preferably 80 to 98 wt%.

[0097] Examples of binders may include polyvinylidene fluoride (PVDF), polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber and various copolymers thereof. Specifically, styrene-butadiene rubber (SBR)-carboxymethyl cellulose (CMC) may be used for high thickening properties.

[0098] Generally, the content of the binder may be 1 to 20 wt %, preferably 1 to 15 wt %, and more preferably 1 to 10 wt %, based on the total weight of solids excluding the solvent in the negative electrode mixture slurry.

[0099] The conductive material is a component for further improving the conductivity of the negative electrode active material, and can be added in an amount of 1 to 20% by weight based on the total weight of the solid in the negative electrode mixture slurry. The conductive material is not particularly limited as long as it has conductivity without causing chemical changes in the battery, and for example, carbon powder such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black can be used; graphite powder such as natural graphite, artificial graphite, or graphite with a very developed crystal structure; conductive fibers such as carbon fibers or metal fibers; conductive powders such as fluorocarbon powders, aluminum powders, and nickel powders; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives; and the like.

[0100] The content of the conductive material may be 1 to 20 wt %, preferably 1 to 15 wt %, and more preferably 1 to 10 wt %, based on the total weight of solids excluding the solvent in the negative electrode mixture slurry.

[0101] The solvent may include water or an organic solvent, such as N-methyl-2-pyrrolidone (NMP), and its use amount may be such that a preferred viscosity is achieved when a negative electrode active material and an optional binder and a conductive material are included. For example, the content of the solvent may be such that the concentration of the solid including the negative electrode active material and the optional binder and conductive material is 50 wt % to 95 wt %, preferably 70 wt % to 95 wt %, preferably 70 wt % to 90 wt %.

[0102] When the metal itself is used as the negative electrode, the negative electrode can be manufactured by physically combining, rolling or depositing the metal on the metal film itself or the negative electrode current collector. The deposition method can be electrochemical deposition or chemical vapor deposition.

[0103] For example, the metal film itself, or the metal bonded / rolled / deposited on the negative electrode current collector, can be one metal selected from the group consisting of lithium (Li), nickel (Ni), tin (Sn), copper (Cu) and indium (In) or an alloy of two of these metals.

[0104] (3) Diaphragm

[0105] In addition, as a separator, a commonly used porous polymer film commonly used as a separator can be used alone, for example, a porous polymer film made of polyolefin-based polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers, or a laminate thereof can be used. Alternatively, a commonly used porous non-woven fabric can be used, for example, a non-woven fabric made of high melting point glass fiber or polyethylene terephthalate fiber, but the present invention is not limited thereto. Moreover, a coated separator including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used in a single-layer or multilayer structure.

[0106] Specifically, the separator included in the electrode assembly of the present invention may be a safety reinforced separator (SRS) in which a coating layer containing a ceramic component or a polymer material is formed to ensure heat resistance or mechanical strength.

[0107] Specifically, the diaphragm included in the electrode assembly of the present invention comprises a porous diaphragm substrate and a porous coating completely coated on one surface or both surfaces of the diaphragm substrate, wherein the coating may comprise a mixture of inorganic particles selected from metal oxides, metalloid oxides, metal fluorides, metal hydroxides and combinations thereof, and a binder polymer for connecting and fixing the inorganic particles to each other.

[0108] The coating may include one or more selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, and MgF as inorganic particles. Here, the inorganic particles can improve the thermal stability of the separator. That is, the inorganic particles can prevent the separator from shrinking at high temperatures. In addition, the binder polymer can improve the mechanical stability of the separator by fixing the inorganic particles.

[0109] The external shape of the lithium secondary battery of the present invention is not particularly limited, but may be cylindrical using a can, square, pouch, or coin-shaped, or the like.

[0110] Hereinafter, the present invention will be described in more detail with reference to specific embodiments. However, the following examples are only for illustrative purposes, so as to facilitate understanding of the present invention, and do not limit the scope of the present invention. It will be apparent to those skilled in the art that various changes and modifications may be made without departing from the scope and spirit of the present invention, and it is apparent that such changes and modifications are within the scope of the appended claims.

[0111] Example

[0112] Example 1

[0113] (Manufacturing of non-aqueous electrolyte)

[0114] LiPF6 was dissolved in an organic solvent (ethylene carbonate (EC): propylene carbonate (PC): ethylene propionate (EP): propyl propionate (PP) = 20:10:25:45 volume ratio) to 1.2 M to prepare a non-aqueous solvent, and 0.5 g of hexamethylene diisocyanate and 1 g of lithium difluoro(oxalate)borate (LiODFB) were introduced into 98.5 g of the non-aqueous solvent to prepare a non-aqueous electrolyte.

[0115] (Manufacturing of lithium secondary batteries)

[0116] The positive electrode active material (LiCoO2), conductive material (carbon black), binder (polyvinylidene fluoride) were added to N-methyl-2-pyrrolidone (NMP) as a solvent at a weight ratio of 97.5:1.3:1.2 to prepare a positive electrode slurry (solid content of 74 wt%). The positive electrode slurry was coated on one surface of a positive electrode current collector (Al film) with a thickness of 15 μm, dried and rolled to manufacture a positive electrode.

[0117] The negative electrode active material (graphite: SiO = 92: 8 weight ratio), the conductive material (carbon black), and the binder (polyvinylidene fluoride) were added to N-methyl-2-pyrrolidone (NMP) as a solvent at a weight ratio of 96.8: 0.2: 3.0 to prepare a negative electrode slurry (solid content of 62 weight %). The negative electrode slurry was coated on one surface of a negative electrode current collector (Cu film) with a thickness of 15 μm, dried and rolled to manufacture a negative electrode.

[0118] In a drying room, a polyolefin-based porous separator coated with inorganic particles Al2O3 was placed between the positive electrode and the negative electrode manufactured as described above, and then the prepared nonaqueous electrolyte was injected therein to manufacture a secondary battery.

[0119] Example 2

[0120] A secondary battery was manufactured in the same manner as in Example 1, except that 1 g of hexamethylene diisocyanate and 1 g of lithium difluoro(oxalato)borate (LiODFB) were introduced into 98 g of the nonaqueous solvent prepared in Example 1 to prepare a nonaqueous electrolyte.

[0121] Example 3

[0122] A secondary battery was manufactured in the same manner as in Example 1, except that 2 g of hexamethylene diisocyanate and 1 g of lithium difluoro(oxalato)borate (LiODFB) were introduced into 97 g of the nonaqueous solvent prepared in Example 1 to prepare a nonaqueous electrolyte.

[0123] Example 4

[0124] A secondary battery was manufactured in the same manner as in Example 1, except that 0.5 g of hexamethylene diisocyanate and 1 g of lithium difluoro(oxalato)borate (LiODFB) were introduced into 97.5 g of the nonaqueous solvent prepared in Example 1 to prepare a nonaqueous electrolyte.

[0125] Example 5

[0126] A secondary battery was manufactured in the same manner as in Example 1, except that 2 g of hexamethylene diisocyanate and 0.5 g of lithium difluoro(oxalato)borate (LiODFB) were introduced into 97.5 g of the nonaqueous solvent prepared in Example 1 to prepare a nonaqueous electrolyte.

[0127] Comparative Example 1

[0128] A secondary battery was manufactured in the same manner as in Example 1 above, except that 100 g of the nonaqueous solvent prepared in Example 1 above was used to prepare the nonaqueous electrolyte.

[0129] Comparative Example 2

[0130] A secondary battery was manufactured in the same manner as in Example 1 above, except that 0.5 g of hexamethylene diisocyanate was introduced into 99.5 g of the nonaqueous solvent prepared in Example 1 above to prepare a nonaqueous electrolyte.

[0131] Comparative Example 3

[0132] A secondary battery was manufactured in the same manner as in Example 1 above, except that 1 g of lithium difluoro(oxalato)borate (LiODFB) was introduced into 99 g of the nonaqueous solvent prepared in Example 1 above to prepare a nonaqueous electrolyte.

[0133] Comparative Example 4

[0134] LiPF6 was dissolved in an organic solvent (ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) = 30:30:40 volume ratio) to 1.2 M to prepare a non-aqueous solvent, and 0.5 g of hexamethylene diisocyanate and 1 g of lithium difluoro(oxalate)borate (LiODFB) were introduced into 98.5 g of the non-aqueous solvent to prepare a non-aqueous electrolyte.

[0135] A secondary battery was manufactured in the same manner as in Example 1 described above, except that the above-described nonaqueous electrolyte was used.

[0136] Experimental Example 1 - Determination of Co Dissolution by ICP Analysis

[0137] For each of the secondary batteries manufactured in Examples 1 to 5 and Comparative Examples 1 to 4, the Co dissolution amount D0 was measured, and the Co dissolution amount D0 after storage at 85° C. for 8 hours was measured. t .

[0138] Specifically, for each of the batteries manufactured in Examples 1 to 5 and Comparative Examples 1 to 4, the amount of Co elution was analyzed using an ICP analysis method before and after storage at 85° C. for 8 hours.

[0139] [Table 1]

[0140] <![CDATA[D t / D0]]> Example 1 2.40 Example 2 2.04 Example 3 1.76 Example 4 2.54 Example 5 1.56 Comparative Example 1 13.5 Comparative Example 2 6.3 Comparative Example 3 13.0 Comparative Example 4 7.8

[0141] Experimental Example 2 - Determining the pH of the electrolyte

[0142] For each of the secondary batteries manufactured in Examples 1 to 5 and Comparative Examples 1 to 4, the pH of the nonaqueous electrolyte after storage at 60° C. for 1 week was measured.

[0143] [Table 2]

[0144] pH Example 1 4.5 Example 2 4.7 Example 3 5.1 Example 4 4.3 Example 5 5.0 Comparative Example 1 2.8 Comparative Example 2 4.1 Comparative Example 3 3.2 Comparative Example 4 3.8

[0145] Experimental Example 3-Evaluation of High Temperature Cycle Performance

[0146] For each of the secondary batteries manufactured in Examples 1 to 5 and Comparative Examples 1 to 4, the cycle performance was evaluated.

[0147] Specifically, the batteries manufactured in the above Examples 1 to 5 and Comparative Examples 1 to 4 were each charged to 4.5V at a constant current of 0.5C at 45°C, and then discharged to 3.0V at a constant current of 0.5C, which was set as one cycle, and then 200 charge / discharge cycles were performed to measure the capacity retention rate based on the initial capacity after 1 cycle. The results are shown in Table 3 below.

[0148] [Table 3]

[0149] Capacity retention rate (%) Example 1 93.2 Example 2 91.8 Example 3 89.3 Example 4 93.0 Example 5 90.1 Comparative Example 1 85.6 Comparative Example 2 86.8 Comparative Example 3 87.1 Comparative Example 4 85.7

[0150] As shown in Table 3, compared with the secondary batteries of Comparative Example 1 which includes neither the additive of Formula 1 nor LiODFB, Comparative Example 2 which does not include LiODFB, and Comparative Example 3 which does not include the additive of Formula 1, Examples 1 to 5 which use a combination of the diisocyanate additive of Formula 1 and LiODFB have a high capacity retention rate and are therefore excellent in life performance.

[0151] In addition, compared with Comparative Example 4 using a combination of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC), Examples 1 to 5 using a non-aqueous electrolyte including an organic solvent of ethylene carbonate (EC), propylene carbonate (PC), ethylene propionate (EP) and propyl propionate (PP) have a high capacity retention rate and are therefore excellent in life performance.

[0152] Experimental Example 4-Evaluation of High Temperature Storage Performance

[0153] For each of the secondary batteries manufactured in Examples 1 to 5 and Comparative Examples 1 to 4, high-temperature storage performance was evaluated.

[0154] Specifically, the secondary batteries of Examples 1 to 5 and Comparative Examples 1 to 4 described above were each fully charged to 4.5 V and then stored at 85° C. for 8 hours.

[0155] Before storage, the capacity of each fully charged secondary battery was measured and then set as the initial capacity of the secondary battery.

[0156] After 8 hours, the capacity of each stored secondary battery was measured to calculate the capacity reduced during the storage period. The percentage ratio of the reduced capacity to the initial capacity of the secondary battery was calculated to obtain the capacity retention rate after 8 hours. The results are shown in Table 4 below.

[0157] [Table 4]

[0158] Capacity retention rate (%) Example 1 92.4 Example 2 92.6 Example 3 92.1 Example 4 91.8 Example 5 93.2 Comparative Example 1 86.8 Comparative Example 2 90.1 Comparative Example 3 88.3 Comparative Example 4 85.6

[0159] As shown in Table 4 above, compared with the secondary batteries of Comparative Example 1 which includes neither the additive of Formula 1 nor LiODFB, Comparative Example 2 which does not include LiODFB, and Comparative Example 3 which does not include the additive of Formula 1, Examples 1 to 5 which use a combination of the diisocyanate additive of Formula 1 and LiODFB have a high capacity retention rate after high temperature storage, and thus exhibit stable performance at high temperatures.

[0160] In addition, compared with Comparative Example 4 using a combination of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC), Examples 1 to 5 using a non-aqueous electrolyte including an organic solvent of ethylene carbonate (EC), propylene carbonate (PC), ethylene propionate (EP) and propyl propionate (PP) have a high capacity retention rate after high-temperature storage, thereby exhibiting stable performance at high temperatures.

Claims

1. A non-aqueous electrolyte comprising a lithium salt, an organic solvent and an additive, wherein: The additive includes a compound represented by the following formula 1 and lithium difluoro(oxalato)borate (LiODFB); and The organic solvent includes ethylene carbonate (EC), propylene carbonate (PC), ethylene propionate (EP) and propyl propionate (PP): [Formula 1] In the above formula 1, n is an integer of 3 to 10.

2. The nonaqueous electrolyte according to claim 1, wherein In Formula 1, n is an integer of 3 to 8.

3. The nonaqueous electrolyte according to claim 1, wherein The lithium salt includes LiPF6.

4. The nonaqueous electrolyte according to claim 1, wherein The compound represented by Formula 1 may be included in an amount of 0.1 wt % to 5 wt % based on the total amount of the nonaqueous electrolyte.

5. The nonaqueous electrolyte according to claim 1, wherein The content of the lithium difluoro(oxalato)borate (LiODFB) is 0.1 wt % to 5 wt % based on the total amount of the non-aqueous electrolyte.

6. The nonaqueous electrolyte according to claim 1, wherein The weight ratio of the compound represented by Formula 1 to the lithium difluoro(oxalato)borate (LiODFB) is 0.2:1 to 5:

1.

7. A lithium secondary battery comprising: positive electrode; negative electrode; as well as The nonaqueous electrolyte according to any one of claims 1 to 6, Wherein, the upper limit of the operating voltage of the lithium secondary battery is above 4.47V.

8. The lithium secondary battery according to claim 7, wherein: The positive electrode includes a lithium cobalt-based oxide as a positive electrode active material.

9. The lithium secondary battery according to claim 7, wherein: The negative electrode comprises graphite and SiO x As negative electrode active material, where 0≤x<2.

10. The lithium secondary battery according to claim 7, wherein: The lithium secondary battery satisfies the following relationship (1): Relation (1): D t / D0<5 In equation 1, D t is the amount of Co dissolved in the non-aqueous electrolyte measured after the lithium secondary battery was stored at a high temperature of 85° C. for 8 hours, and D0 is the amount of Co dissolved in the non-aqueous electrolyte of the lithium secondary battery before high-temperature storage.

11. The lithium secondary battery according to claim 7, wherein: The pH of the non-aqueous electrolyte of the lithium secondary battery measured after being stored at 60° C. for 1 week is greater than 4.

Citation Information

Patent Citations

  • Braking system for a vehicle having a collapsible operating pedal in the event of a collision and a method of operating the braking system

    KR1020220110317A